The Influence of TGT Type Cooperative Learning through Jellyfish Hunting Games on Science Collaboration Ability - Rolila Faradizah; Herwin; Nimas Vindy Armadyaningtyas (Postgraduate, University of Mataram, 2024)
This study aims to determine the significance of the effect of implementing the TGT-type cooperative learning model on the science collaboration abilities of fourth-grade elementary school students on photosynthesis material. The method in this research is a quantitative method with a pre-experimental model (One Group Pretest-Posttest). The data collection technique used in this study uses non-test techniques, namely questionnaires and student activity observation sheets. Participants in this study were 25 fourth-grade students at SD Muhammadiyah Blawong I. Data analysis used a paired sample t-test. Based on the results of the Paired-Sample T-Test analysis, a Sig value of 0.000 <0.05 was obtained. Because the significant value is smaller than 0.05, is rejected and is accepted. The TGT-type cooperative learning model through a jellyfish hunting game shows significant differences in students' collaboration abilities before and after treatment. The conclusion is that there is a significant effect of implementing the TGT-type cooperative learning model through the jellyfish hunting game on the science collaboration abilities of fourth-grade elementary school students on photosynthesis material.